Being a Psychotherapist in Times of the Novel Coronavirus Disease: Stress-Level, Job Anxiety, and Fear of Coronavirus Disease Infection in More Than 1,500 Psychotherapists in Austria - Probst, Thomas; Humer, Elke; Stippl, Peter; Pieh, Christoph (Frontiers in Psychology, 2020)
This study investigated stress-level, degree of job-related anxiety, and fear of coronavirus disease (COVID-19) infection in psychotherapists in the early weeks of the COVID-19 lockdown in Austria. One thousand five hundred and forty-seven psychotherapists participated in an online survey, assessing stress [Perceived Stress Scale-10 (PSS-10)], work-related worries and fears of existence [Job Anxiety Scale (JAS)], fear of COVID-19 infection during face-to-face psychotherapy, and adherence to five protective measures against COVID-19 infection during face-to-face psychotherapy. Stress-levels were higher than in a representative sample (p < 0.001). When psychotherapy was the sole income, stress-level (p = 0.020) and job anxiety (p < 0.001) were higher. Experiences with teletherapy, the psychotherapy format used during COVID-19, as well as reductions in number of patients treated during COVID-19, had no effect on stress-level or job anxiety. Psychotherapists still conducting face-to-face psychotherapy during COVID-19 reported less fear of infection compared to those conducting no face-to-face psychotherapy (p < 0.001), whereby the fear of infection was further reduced when they were more able to adhere to protective measures against COVID-19 (p < 0.01). Mental hygiene is important for psychotherapists to manage stress and job-related anxiety during COVID-19, especially in those whose income relies on psychotherapy.